Communication with forgetful liars - Philippe Jehiel (Theoretical Economics, 2021)
I consider multi-round cheap talk communication environments in which, after a lie, the informed party has no memory of the content of the lie. I characterize the equilibria with forgetful liars in such settings assuming that a liar's expectation about his past lie coincides with the equilibrium distribution of lies aggregated over all possible realizations of the states. The approach is used to shed light on when the full truth is almost surely elicited, and when multiple lies can arise in equilibrium. Elaborations are proposed to shed light on why non-trivial communication protocols are used in criminal investigations.
Keywords: C72; D82; 330; Forgetful liars; lie detection; analogy-based expectations; cheap talk